IL-17A synergistically stimulates TNF-α-induced IL-8 production in human airway epithelial cells: A potential role in amplifying airway inflammation. (20th April 2016) - Honda, Kojiro; Wada, Hiroo; Nakamura, Masuo; Nakamoto, Keitaro; Inui, Toshiya; Sada, Mitsuru; Koide, Takashi; Takata, Saori; Yokoyama, Takuma; Saraya, Takeshi; Kurai, Daisuke; Ishii, Haruyuki; et al.
ABSTRACT: Background: Recent reports have suggested an involvement of neutrophilic inflammation driven by interleukin (IL)-17 from Th17 cells, especially in severe, refractory asthma. It remains unknown about the possible interactions of this cytokine and other proinflammatory cytokines to direct neutrophilic airway inflammation.Materials and Methods: We evaluated the effects of IL-17A, IL-17E, and IL-17F in combination with other stimuli such as tumor necrosis factor (TNF) –α on the production and expression of IL-8 in human bronchial epithelial cells. We also studied their effects on other cytokine production. The possible role of mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) signaling pathways was evaluated by specific inhibitors. We examined the effects of anti-asthma drugs, such as steroids or salmeterol.Results: IL-17A alone induced only a minimal effect on IL-8 expression. IL-17A, but not IL-17E or IL-17F, in combination with TNF-α showed a synergistic effect on IL-8 expression. Similar findings were found when combination with IL-1β and IL-17A were used, but such was not the case with lipopolysaccharide (LPS). In addition, we further found such synergy on GM-CSF production. The synergy with TNF-α and IL-17A was significantly inhibited by MAPKs inhibitors. Corticosteroids such as fluticasone propionate and dexamethasone, but not salmeterol, partially suppressed the IL-17A and TNF-α-induced IL-8 production.Conclusions: IL-17A in the combination with TNF-α or IL-1β showed a synergistic augmenting effect on IL-8 and GM-CSF production in human airway epithelial cells.